Pemertahanan Bahasa Jawa Santri Pondok Pesantren Durrotu Ahlissunnah Waljamaah Banaran Gunungpati Semarang - sih, Sri Ning; Kurniati, Endang; M.Pd., Widodo (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
AbstractJavanese language as a regional language along with the development era is starting to be forgotten. Various attempts to maintain language are carried out as a preservation effort so that Javanese language is not extinct. This study describes the problem of Javanese language retention in Durrotu Ahlissunnah Waljamaah Islamic Boarding School students. The research method used is descriptive qualitative research data source of speech by students of Islamic Boarding School Durrotu Ahlissunnah Waljamaah. The data used is a fragment of the speech of students of the Islamic Boarding School Durrotu Ahlissunnah Waljamaah. Data collection techniques using record techniques and note taking techniques. The results of the analysis can be concluded: (1) Javanese language retention Santri Islamic Boarding School Durrotu Ahlissunnah Waljamaah consists of two forms, namely (a) a form of active detention that is the use of Javanese as a whole in which no other languages are mixed, and (2) a form of passive retention that is a form of language retention characterized by the use of Javanese but containing one foreign language element or the use of other languages but there is Javanese in it.Keywords: language retention, boarding school.